An overview of endometrial cancer risk factors - Żychoń , Piotr; Prajwos , Eryk; Janawa, Kamil; Tomaszek , Michał; Domagała, Małgorzata; Cękalska, Klaudia; Stenka, Wiktoria (Journal of Education, Health and Sport, 2024)
In developed countries, endometrial cancer is the most common form of invasive gynecological cancer. Endometrial cancer is rare in less developed countries where there are fewer common risk factors, but the specific mortality rate is higher. The histological types of endometrial cancers show significant differences in prognosis. The first type of lesions is usually responsive to hormones, at a low stage, and has an excellent outlook, while the second type consists of high-grade tumors that are prone to recurrence, even at an early stage. The majority of endometrial cancers are influenced by hormones, with estrogen playing a role in promoting cancer through its interaction with estrogen receptor α (ER). Obesity is one of the most significant and common risk factors for endometrial cancer. Women who are obese have a three times higher risk of developing endometrial cancer. Many nonobese women can develop PCOS despite obesity being a risk factor, and many obese women may not show signs of PCOS. PCOS involves more than just a decrease in progesterone; progesterone levels may not always be lowered, and other hormone levels can also be impacted. Women affected by infertility may be more at risk for endometrial cancer, particularly if affected by ovulatory disorders. The expression of G-protein coupled estrogen receptor 1 (GPER-1) explains the estrogen-agonistic effect of tamoxifen in endometrial cancers. Tamoxifen and other "antiestrogens" act as pure agonists for GPER-1, a membrane-bound estrogen receptor. Besides genetic predisposition syndromes such as Lynch syndrome and Cowden syndrome, the development of endometrial cancer is associated with risk factors related to estrogen signaling as the main contributing factor. It’s important to create prevention strategies by understanding the key risk factors and how they are involved in the formation of tumors.